Influence of dental status on postoperative complications in major visceral surgical and organ transplantation procedures—the bellydent retrospective observational study - Spitzner, Anastasia; Mieth, Markus; Langan, Ewan Andrew; Büchler, Markus W.; Michalski, Christoph; Billmann, Franck (Langenbeck's archives of surgery, 2024)
The significance of dental status and oral hygiene on a range of medical conditions is well-recognised. However, the correlation between periodontitis, oral bacterial dysbiosis and visceral surgical outcomes is less well established. To this end, we study sought to determine the influence of dental health and oral hygiene on the rates of postoperative complications following major visceral and transplant surgery in an exploratory, single-center, retrospective, non-interventional study.